Differential Morbidity in Preterm Small versus Appropriate for Gestational Age: Perhaps Unverifiable - Marrs, Caroline C.; Mendez-Figueroa, Hector; Hammad, Ibrahim A.; Chauhan, Suneet P. (American Journal of Perinatology, 2015)
Objective The objective of this study was to determine the morbidity of preterm small for gestational age (SGA) infants compared with appropriate for GA (AGA).Study Design This is a secondary analysis of the randomized trial evaluating magnesium sulfate for the prevention of cerebral palsy (CP). We compared outcomes of preterm (< 37 weeks) nonanomalous infants who were SGA (birth weight < 10% for GA) versus AGA (birth weight 10–89% for GA). We compared (1) the parent trial primary outcome, a composite of stillbirth, infant death by 1 year of age, or moderate to severe CP at 2 years of age and (2) composite neonatal morbidity (CNM).Results Of the 1,948 infants who met inclusion criteria, 95% were AGA and 5% were SGA. The primary outcome was similar (10 and 15%, p = 0.08), as was the CNM (24 and 25%, p = 0.89). Sample size calculations indicate that detection of a one-third higher rate of CNM among SGA compared with AGA infants requires more than 93,900 preterm births; for a one-third difference in moderate to severe CP, more than 1.4 million infants.Conclusion Owing to the prohibitive sample size required, ascertaining a difference in sequela between preterm SGA and AGA infants is possibly unverifiable.
Keywords: preterm birth; small for gestational age; neonatal morbidity; cerebral palsy